(3OjhGf GdUQUQjs - (3jMji Hf jhSa Hf jMji GdCfUGQj, GdUQUQj, LeGd GdOjf CHh RcQjG,J (B656 (3g` s
(3ChdgG (B:s
(3bGd GdTjN GdEeGe GdYGde GdaGVd jeOM GdfHj Udi Gddg Ydjg hSde bGajI GdgeRI(B: (3SHMGf ef GddhQi aj CQVg PQC hCMSf GdUfY HGdEJbGf EP HQC s
(3BNQgG (B:s
(3jGQH hCLYd Edi GdNjQGJ efJbdi hfLfj ef VQGe Xd edJXjG Je GdOjhGf GdeHGQc HMeO Gddg hYhfg s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B177 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B236 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B523s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B141 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B797s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdHMhK (B- (3LhJG CdeGfjG GdTQbjI (B(2272) s
Keywords: (3GdCOHs